PENGARUH NILAI TUKAR, SUKU BUNGA SERTIFIKAT BANK INDONESIA DAN INDEKS SAHAM DOW JONES TERHADAP INDEKS HARGA SAHAM GABUNGAN INDONESIA - SATRIO WIBOWO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2012)
Accurate assessment in analyzing the rise and fall of IDX composite index assists investors in minimizing risk while helping to gain profit in the stock market. In this study to prove whether there is influence of exchange rate (rupiah / U.S. ), SBI rate and Dow Jones stock index in New York Stock Exchange on movement of IDX Composite Index. The result of the research showed that exchange rate (rupiah/U.S.), SBI rate and Dow Jones stock index in New York Stock Exchange have effect on movement of IDX Composite Index.